Chaotic hiding and its positive definite blind extraction algorithm of speech signal - Er-fu WANG; Yuan-shuo ZHENG; Xin-wu CHEN; Xiao-zhen LIU (Tongxin xuebao)
The wavelet transform was used to extract energy accumulation zone of speech signal hidden in the chaotic carrier signal for transmission,and a blind extraction algorithm was designed to achieve speech signal extraction under different chaotic dynamical systems.Using three different dimensions of the chaotic dynamic system as the background,simulation experiment analysed the performance of the proposed algorithm in aqualitative and quantitative ways,and verified the algorithm's reliability under the noise environment that prove the blind extraction algorithm can be used as an effective method of security verification of chaotic secure communication system.